2008
DOI: 10.1039/b716851a
|View full text |Cite
|
Sign up to set email alerts
|

Separation of mitochondria by flow field-flow fractionation for proteomic analysis

Abstract: Flow field-flow fractionation (FlFFF) has been utilized for size-based separation of rat liver mitochondria. Collected fractions of mitochondria of various sizes were examined by confocal microscopy, and mitochondria of each fraction were lysed and analyzed by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) for the comparison of protein patterns in differently sized mitochondria by densitometric measurements, and for protein characterization of some gel spots with nanoflow liquid chromatography-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…Uranium carbonate and hydroxide passed through the FFF membrane. AsFlFFF was also used to fractionate micron sized bioparticles and utilised as pre-analytical technique for the characterization of size-dependent proteome patterns [31,33,52]. Additional studies on the applicability of AsFlFFF in proteomics can be found elsewhere [11,53].…”
Section: Micron and Submicron Sized Bioparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uranium carbonate and hydroxide passed through the FFF membrane. AsFlFFF was also used to fractionate micron sized bioparticles and utilised as pre-analytical technique for the characterization of size-dependent proteome patterns [31,33,52]. Additional studies on the applicability of AsFlFFF in proteomics can be found elsewhere [11,53].…”
Section: Micron and Submicron Sized Bioparticlesmentioning
confidence: 99%
“…The system was applied to the analysis and characterization of intact proteins. At the moment the interest in the off-line coupling of conventional or miniaturized AsFlFFF with nanoflow LC-ESI-MS-MS is emerging progressively [11,31,[51][52][53][54]. The protein fractions collected off-line can be digested followed by peptide analysis carried out by nLC-ESI-MS-MS for shotgun analysis.…”
Section: Detection Techniques Used In Asymmetrical Flow Field-flow Frmentioning
confidence: 99%
“…Besides affinity based methods to remove high abundance proteins from a particular sample, subcellular fractionation has been used to reduce complexity of a sample while at the same time retaining information about the cellular location of proteins identified from such an organelle fraction. Current fractionation technologies include density gradient centrifugation and free flow electrophoresis (FFE) 85,86 , which are tedious to perform, require high investments or dilute the sample in an in-acceptable way. Chip-based isoelectric separation was reported, yet amount of organelle was too low for further analysis with 2D-PAGE 10 .…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…However, it may also be accomplished by magnetic capture [3037], free flow electrophoresis [38, 39], flow field-flow fractionation [40], fluorescent organelle sorting [41, 42], laser capture microdissection [43], and dielectrophoresis [44]. Because fractionation protocols have been reviewed recently [1, 7, 45], here we include only reports that were not included in these reviews.…”
Section: Organelle Fractionationmentioning
confidence: 99%